Potential of Candida glabrata from ragi as a bioethanol producer using selected carbohydrate substrates - Micky Vincent; Queentety Johnny; Dayang Salwani Awang Adeni; Nurashikin Suhaili (Smujo International, 2021)
Abstract. Vincent M, Johnny Q, Adeni DSA, Suhaili N. 2021. Potential of Candida glabrata from ragi as a bioethanol producer using selected carbohydrate substrates. Nusantara Bioscience 13: 1-10. The flexibility and efficiency of fermenting microorganisms to convert substrates to ethanol are important factors in achieving high bioethanol yields during ethanolic fermentation. In this study, Candida glabrata, a common yeast found in fermented food, was evaluated in terms of its capability to produce ethanol using different types of carbohydrates, which included simple saccharides (glucose, maltose, sucrose), polysaccharides (starch and cellulose) and complex carbohydrates (total sago effluent, TSE). Our results indicated that C. glabrata was able to efficiently produce ethanol from glucose at 79.84% TEY (Theoretical Ethanol Yield). The ethanol production from sucrose was low, which was only 6.44% TEY, while no ethanol was produced from maltose. Meanwhile, for complex carbohydrate substrates such as starch and cellulose, ethanol was produced only when supplementary enzymes were introduced. Simultaneous Saccharification and Fermentation (SSF) of starch dosed with amylases resulted in an ethanol yield of 55.08% TEY, whilst SSF of cellulose dosed with cellulases yielded a TEY of 31.41%. When SSF was performed on TSE dosed with amylases and cellulases, the highest ethanol production was recorded within 24 h, with a yield of 23.36% TEY. Lactic acid and acetic acid were found to be at minimal levels throughout the fermentation period, indicating an efficient ethanol conversion. A notable increase in C. glabrata biomass was observed in cultures fed with glucose, starch (with supplementary amylases), and TSE (with supplementary amylases and cellulases). The current study indicates that C. glabrata can be used for bioethanol production from glucose, polysaccharides, and complex starchy lignocellulosic substrates such as TSE via SSF.